The Effect of Using Microblogs on the Academic Achievement among 5th Grade Students in Jordan in Science Subject and their Classroom Interaction - Rozan Albesbes; Majed Abu Jabber (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at exploring the effect of using microblogging on the achievement and classroom interaction in science courses among fifth-grade students in Jordan. A Quasi-experimental approach was used. The study sample consisted of (30) male and female students who were randomly distributed into two groups: experimental, who studied using microblogs, and controlled, who studied traditionally. An achievement test was applied to the two groups after computing its validity and reliability. Observing students' classroom interaction of the two groups was also conducted using the Flanders Decimal scale. Using ANOVA, the findings indicated that there is a statistically significant difference at (α= 0.05) in the means between the experimental and the control groups attributed to the teaching method in favor of the experimental group studied using microblogging. The study recommended encouraging teachers to use microblogging in science teaching because they raise the level of achievement and classroom interaction among students, as well as conducting more studies aimed at using microblogging and applying them to other subjects and different stages of study.